Clinical care classification (CCC) system manual : a guide to nursing documentation - Saba, Virginia K. (Springer, 2007)
Designated a Doody's Core Title!. The Preeminent Nursing Terminology Classification System. "The Clinical Care Classification (CCC) System described in this manual is the only standard coded nursing terminology that is based on sound research using the nursing process model framework and that meets the Patient Medical Record Information (PMRI) comparability requirement. The CCC System allows patient care data generated by nurses to be incorporated into the PMRI database, and enables nurses' contributions to patient outcomes to be studied and acknowledged."--The Foreword by Sh